Heteroscedastic probit model: An application of home ownership in Turkey - (:unkn) unknown (My University, 2012)
This study examines the factors affecting the possibility of owning a house in Turkey using probit models. Moreover, it focuses on the heteroscedasticity problem that is ignored in most of the probit applications. The results obtained from the study indicate that besides the demographic characteristics of the head of the household, education, employment, and income are also influential factors in regard to home ownership. Besides these things, evidence indicates that the choice to live in either rural or urban areas has a significant impact on home ownership.
Keywords: Heteroscedastic probit; Heteroscedasticity; Home ownership; Probit